2021
DOI: 10.1002/adma.202008068
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Motion of Charged Domain Walls and Associated Negative Capacitance in Copper–Chlorine Boracite

Abstract: At lower temperatures (≈255 K [1] ), however, the original high-symmetry para electric-orthorhombic state is restored. Symmetry associated with this re-entrant phase transition has unusually, therefore, increased on cooling. Some observations show that this generates a local dip in the heat capacity, [1,2] stalling entropy reduction on decreasing temperature. [1] Strange symmetry transformations also occur in flux-grown barium titanate crystals, where highly ordered "Forsbergh Patterns" can first appear and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Although cAFM images were crucial for igniting wider interest in the topic, the technique has been a bit of a mixed blessing. On the one hand, cAFM has allowed the research community to discover conducting domain walls across a range of ferroelectric materials rather easily: from perovskite or perovskite-like oxides [6][7][8][9] to rare-earth manganites [10,11], boracites [12,13] and Ruddlesden-Popper systems [14]. In addition, because cAFM and piezo-response force microscopy (PFM) can readily be done on the same microstructural region, the technique has allowed the importance of domain wall polarisation discontinuities, for enhanced conductivity, to be clearly revealed [10,15].…”
Section: Transport Physics Of Conducting Domain Wallsmentioning
confidence: 99%
“…Although cAFM images were crucial for igniting wider interest in the topic, the technique has been a bit of a mixed blessing. On the one hand, cAFM has allowed the research community to discover conducting domain walls across a range of ferroelectric materials rather easily: from perovskite or perovskite-like oxides [6][7][8][9] to rare-earth manganites [10,11], boracites [12,13] and Ruddlesden-Popper systems [14]. In addition, because cAFM and piezo-response force microscopy (PFM) can readily be done on the same microstructural region, the technique has allowed the importance of domain wall polarisation discontinuities, for enhanced conductivity, to be clearly revealed [10,15].…”
Section: Transport Physics Of Conducting Domain Wallsmentioning
confidence: 99%
“…Additionally, the wall's internal structure and large polarizability were also suggested to play a key role in obtaining negative capacitances. A recent study, [ 164 ] in yet another wall‐based mechanism, intriguingly showed that charged 90° domain walls in the improper ferroelectric copper–chlorine boracite move opposite to the driving electric field direction. This anomalous wall motion leads to a measurable negative contribution to the overall dielectric response.…”
Section: State‐of‐the‐art Knowledgementioning
confidence: 99%
“…However, the growth of large single crystals 6,7 is difficult and with the development of perovskite oxide ceramic materials possessing diverse functional properties, interest in the boracite family subsequently waned. Recently, however, the discoveries surrounding improper ferroelectrics [8][9][10] and their associated charged domain walls 11,12 has rekindled interest in the potential of boracites as functional materials. The charged domain walls in Cu-Cl boracite are particularly remarkable: they present either enhanced conductivity (in 90°tail-to-tail walls) or reduced conductivity (in 90°head-to-head walls) relative to the bulk 12 .…”
mentioning
confidence: 99%
“…Uniquely, head-to-head charged walls have been shown to have an unconventional electrostatic response (moving in the opposite direction to that expected under an applied electric field), consistent with the existence a) Also at School of Mathematics and Physics, Queen's University Belfast, Belfast, BT7 1NN, United Kingdom. b) Also at Maxwell Centre, Cavendish Laboratory, University of Cambridge, Cambridge, United Kingdom of negative capacitance 11 . This discovery of new properties at domain walls prompts our understanding of the intrinsic properties of boracites to be revisited.…”
mentioning
confidence: 99%
See 1 more Smart Citation